PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, MODERNISASI ADMINISTRASI PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada UMKM Batik di Pasar Klewer Surakarta) - Setyani, Meilina Tri; Harimurti, Fadja; Suharno, Suharno (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2022)
This study aims to examine the effect of understanding of tax regulations, modernizing tax administration and tax sanctions on individual taxpayers compliance in paying their personal taxes. This study uses a survey method. Sources of data using primary data, namely questionnaires. The object of the research was the individual taxpayers of batik SMEs in Pasar Klewer Surakarta. The population in this study were 2.576 batik SMEs in Pasar Klewer who had NPWP. The sampling technique uses the slovin formula as many as 130 respondents. The data analysis technique uses descriptive statistics, validity and reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination (R 2) test. The results of this study indicate that the understanding of tax regulations has no effect on individual taxpayer compliance, while modernization of tax administration and tax sanctions has a positive and significant effect on individual taxpayer compliance. Future research is expected to expand the object of research and use other independent variables.